The influence of timing and planting proportion on the intraspecific competitiveness ability of drunken horse grass (Achnatherum inebrians (Hance) Keng) by fungal endophyte infection - Jianxin Cao; Xiang Yao; Xuekai Wei; Ruochen Zhang; Jing Liu; Chunjie Li (Plant, Soil and Environment, 2024)
Drunken horse grass (Achnatherum inebrians (Hance) Keng) is a toxic perennial bunchgrass native to Northwestern China. Epichloë endophytic fungi infection could enhance the stress tolerance of drunken horse grass. However, there is a scarcity of literature regarding the effects of intraspecific competition. As a result, we anticipated that the intraspecific competitive dynamics between endophyte-infected (EI) and endophyte-free (EF) plants would become more transparent for four years by planted as the proportions of 2:1, 1:1, and 1:2. The results showed the EI plants exhibited more biomass, seed yields, and survival rates than EF plants. Endophyte infection also facilitated a competitive advantage by enhancing photosynthesis and soil nutrition. Our findings constituted the inaugural investigation into the influence of the intraspecific competitive ability of grass infected with Epichloë endophyte fungi. EI plants caused them to become stronger and stronger, while EF became weaker and weaker by timing and planting proportion increasing, and EF drunken horse grass could be replaced by EI. These conclusions were instrumental in elucidating why the endophytic fungal infection rate of drunken horse grass is 100% observed in natural wilderness. Epichloë endophyte could reduce plant diversity and enhance the dominance of EI plants in intraspecific competition; drunken horse grass may be threatening the persistence of native plant species.